2018
DOI: 10.1002/cncr.31404
|View full text |Cite
|
Sign up to set email alerts
|

Impact of psychiatric illness on decreased survival in elderly patients with bladder cancer in the United States

Abstract: One-half of patients with muscle-invasive bladder cancer who underwent treatment were diagnosed with a psychiatric disorder, which resulted in worse survival outcomes compared with patients who did not have a posttreatment psychiatric diagnosis. This information can be used to inform interventions to educate patients with muscle-invasive bladder cancer regarding the impact of different treatments on mental health. Cancer 2018. © 2018 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
35
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 43 publications
(100 reference statements)
3
35
1
Order By: Relevance
“…The most interesting finding by Jazzar and colleagues is the distribution of psychiatric diagnoses in their cohort. Before reading the article, it would seem reasonable to assume that the most common psychiatric diagnoses affecting a cancer population would be anxiety and depression; yet substance abuse was the most common psychiatric illness noted, affecting almost one‐third (32.5%) of the cohort.…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…The most interesting finding by Jazzar and colleagues is the distribution of psychiatric diagnoses in their cohort. Before reading the article, it would seem reasonable to assume that the most common psychiatric diagnoses affecting a cancer population would be anxiety and depression; yet substance abuse was the most common psychiatric illness noted, affecting almost one‐third (32.5%) of the cohort.…”
mentioning
confidence: 90%
“…17 Early involvement of palliative care services in the care of patients with cancer (even those with localized disease) has produced improvements in the domains of pain and symptom control, reductions in associated depression and anxiety, and reductions in repeat hospital admissions. 18 The most interesting finding by Jazzar and colleagues 6 is the distribution of psychiatric diagnoses in their cohort. Before reading the article, it would seem reasonable to assume that the most common psychiatric diagnoses affecting a cancer population would be anxiety and depression; yet substance abuse was the most common psychiatric illness noted, affecting almost one-third (32.5%) of the cohort.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…4 Additionally, substantial evidence demonstrated that the diagnosis of posttreatment psychiatric disorder resulted in significantly worse overall survival and cancer-specific survival in bladder cancer. 5 Chronic psychological stress has been shown to intervene in immune function and play a role in the tumor growth and progression in diverse carcinomas. [6][7][8] However, the effects of chronic psychological stress on the biological behaviors of bladder cancer and possible underlying mechanisms are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Among men with prostate cancer in Ontario, Canada, those treated with radical prostatectomy had a 49% greater likelihood of receiving antidepressant therapy in the 5 yr following treatment (odds ratio [OR] 1.49, 95% confidence interval [CI] 1.35–1.64), whereas those receiving radiotherapy had a 33% increase in odds (OR 1.33, 95% CI 1.21–1.47), and those treated with active surveillance had a 15% increase in likelihood (OR 1.15, 95% CI 0.94–1.41) [4] . Specific to bladder cancer and the highly comorbid patient population afflicted by this disease, Jazzar et al [5] found that 50.4% of bladder cancer patients in the SEER-Medicare database were diagnosed with a post-treatment psychiatric disorder. In addition, those undergoing radical cystectomy were 19% more likely to be diagnosed with a psychiatric disorder compared to those undergoing chemoradiation.…”
mentioning
confidence: 99%